Geology and environmental change: a New Brunswick perspective - Pronk, A. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1991)
Studies of earth cycles are used in a variety of ways, from mineral exploration to recording and explaining past, and projecting future climate change. Geology helps us find the commodities we need to accommodate our lifestyles, to assess natural hazards, find drinking water and safe places to dispose of our waste. As mankind will search for a way to achieve a globally sustainable society, the limits of this planet will have to be acknowledged. Geology is one of the disciplines that can help us understand our planet and establish those limits. Further research in the earth sciences is required to clarify our present knowledge of the environment, quantify many processes, and define limits of prediction for future change.